Penerapan Plasma Pijar Korona sebagai Teknik Pengawetan Fisika - Nabilah Azka Burhansyah (Bandung Conference Series: Pharmacy, 2022)
Abstract. A new method for decontaminating bacteri with non-thermic plasma at atmospheric pressure has been developed. Corona glow plasma consists of a DC (Directing Current) voltage source as a plasma generator where the plasma phase occurs. In plasma sterilization has been done with Eschericia coli bacteria. These bacteria were planned on a medium and incandescent with corona discarchge plasma. The results showed a decrease in the number of bacterial colonies (CFU/ml). Sterilizing agents present in the plasma atmosphere will cause cell damage, one of which is by changes in lipid membranes caused by fatty acids peroxides. Abstrak. Metoda baru untuk dekontaminasi bakteri dengan plasma non termik pada tekanan atmosfir telah dikembangkan. Plasma pijar korona terdiri dari sumber tegangan DC (Directing Current) sebagai pembangkit plasma dan elektroda titik – bidang tempat fase plasma terjadi. Pada sterilisasi dengan plasma dilakukan dengan bakteri Eschericia coli. Bakteri ini dibiakkan pada media agar dan dipijarkan dengan plasma pijar korona. Hasil menunjukkan penurunan jumlah koloni bakteri (CFU/ml). Agen sterilisasi yang ada pada atmosfir plasma akan menyebabkan kerusakan sel salah satunya dengan perubahan membrane lipid yang disebabkan asam lemak peroksida.